1974
DOI: 10.1149/1.2401815
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Oxygen Activities in Argon-Oxygen Mixtures by Coulometric Titration

Abstract: High-temperature electrochemical cells based on stabilized zirconia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…[10], [11], and [14] it is found that According to Eq. [16] at Po2 < Po2 'nin" (i.e., Cads << 1) mass transport limitation of oxygen atoms occurs at the cathode and according to Eq. [1'7] at Po2 > Po2 rain" (i.e., eads ~ 1) mass transport hmitation of oxygen atoms occurs at the anode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], [11], and [14] it is found that According to Eq. [16] at Po2 < Po2 'nin" (i.e., Cads << 1) mass transport limitation of oxygen atoms occurs at the cathode and according to Eq. [1'7] at Po2 > Po2 rain" (i.e., eads ~ 1) mass transport hmitation of oxygen atoms occurs at the anode.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements were performed in the temperature range 770-1050 K and with N2-O2 mixtures in the oxygen partial pressure range of 10-5-1 atm O2. The oxygen partial pressures in the range of 10-2-1 atm were obtained by mixing appropriate O2/N2 mixtures and in the range of 10-~-10-2 arm by an oxygen pump (15,16). The oxygen partial pressure is measured using an oxygen sensor based on stabilized zirconia.…”
Section: Methodsmentioning
confidence: 99%
“…The verification of Faraday's law has been previously obtained by Fouletier et al (6,10) in their tests of a solid-electrolyte oxygen pump. However, both Fouletier et al (10) and Agrawal et al (11) observed inaccuracies when an electrode was common to both pump and measuring cells in units which were used to simultaneously control and measure oxygen contents in a flowing carrier gas. Therefore, the four-electrode two-cell approach shown in Figure 1 was selected rather than a possible three-electrode arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Yuan and Kr6ger [1] used a three-electrode assembly with a common inner electrode. Agrawal et al [2] and Fouletier et al [3] used a four-electrode assembly in a common furnace. In our laboratory, both the pump and the sensor were set up in two independent furnaces to avoid the electrical interface between them.…”
Section: Methodsmentioning
confidence: 99%